A CASE STUDY OF LEADING AND SUPPORTING TEACHING TEAMS AT A PROGRAMME MANAGEMENT LEVEL FOR A 600+ STUDENT MSC MANAGEMENT PROGRAMME - Sam Buxton (EDULEARN23 Proceedings, 2023)
The MSc Management (and pathways) at Swansea University has seen substantial developments over the past 3 years with a January entry enrolment point being introduced in January 2021. The popularity of this entry point along with the increased popularity of our September entry point and the change in UKVI regulations has led to an explosive increase in student numbers. The current academic year will see the programme enroll over 600 students (mainly international) when combining both entry points. This significant increase in student numbers has also created significant challenges for the academics involved in teaching on this programme. The mental health and wellbeing of staff is of significant importance as the challenges this increase in student numbers has brought is significant. This joint case study relating to the expansion of the team that manages the MSc Management (and pathways).The research will focus on leading and supporting teaching teams from two different viewpoints. It start by giving a brief overview of the evolution of the MSc Management (and pathways) within the School of Management at Swansea University and how it has developed from a 150+ student programme to a 600+ student programme with two enrolment points. As this had meant there needed to be a significant development in the way the programme is led and how staff are supported on it. The research then moves to look at the programme from a leadership perspective looking at how we ensure that all members of the programme management team are operating in a cohesive manner and making sure all staff teaching on the programme have the required support.We have been advocating to the senior leadership teams for more academics because, as it stands, we currently have 60 academics teaching on a programme of over 600 students (but only around 10 academics are involved in the main teaching and the rest are brought in to ensure there is adequate supervision on the dissertation and business project modules). This is a staff ratio of 1:60.This research looks at the ways in which as a programme team we are developing resources to best support the teaching team on the MSc Management. Examples of this include:1. Ensuring adequate resources are in place to deliver modules: for the large compulsory modules that requires exceptionally large teams. These modules are the specialist dissertation or business project modules2. Carrying out staff training as part of CPD (Continuing Professional Development) to ensure that staff are all aligned and have clear guidelines and structure to follow3. Managing multiple markers to ensure consistency in feedback and grade setting4. Putting systems and procedures in place to try and provide consistent responses for all modules.We would like to benefit their well-being and while we are not able to address staff workloads, we feel the measures we are introducing will support their well-being.The case study will highlight the ideas we hope to embed to support both areas while still successfully supporting our students.